How Attitudes, Subjective Norms, and Perceived Behavioral Control Influence Taxpayer Compliance: The Moderating Role of Intention to Comply in Garut District among Individual Taxpayers - Muslim Alkautsar; Hanifah Hanifah; Acep Abdul Basit (Khazanah Sosial, 2023)
The purpose of this article is to examine the influence of attitude, subjective norms, and perceived behavioral control on the compliance of entrepreneur as a taxpayer in Garut, moderated by the intention to comply with taxes. This study is motivated by the failure to achieve tax revenue targets due to the low compliance of entrepreneur taxpayers in reporting because self-assessment system. The methodology uses a quantitative descriptive and verificative approach involving 100 individual entrepreneurs as a taxpayers selected by convenience sampling. The questionnaire gives to the respondent and the analysis tool using path analysis. A positive regression coefficient indicates a direct and positive correlation between Subjective Norms and the Compliance of Individual Taxpayers. This favorable influence may materialize in the form of advice or encouragement for taxpayers to demonstrate compliant behavior. Furthermore, a positive association exists between Perceived Behavioral Control and the Compliance of Individual Taxpayers. Essentially, as the perceived level of control over behavior increases for an individual taxpayer, their compliance also tends to increase. Individual Taxpayer Compliance is influenced by their Attitude without mediation from Tax Compliance Intentions. This suggests that taxpayer compliance behavior may be solely shaped by the taxpayer's favorable attitude towards taxes. These findings suggest that indirectly, subjective norms, through tax compliance intentions, significantly impact individual taxpayer compliance. This test outcome suggests that Tax Compliance Intentions can serve as a moderating variable in this study.